Consumer Product Involvement, Attitude and Cognition Towards Ad, and Perceived Value Concerning Purchase Intentions - Wirya, Yosephine Hannie; Syah, Tantri Yanuar Rahmat (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2022)
An advertisement can be effective if the advertisement content and message conveyed by the marketer are right on target, and consumers are motivated to make a purchase. Where consumer’s purchase intentions are formed from the harmonious integration of various factors, both in terms of products marketed through advertising media to consumer responses themselves after they are exposed to advertising impressions. This study is based on a survey of 135 online respondents in Indonesia. The proposed hypotheses were tested using Structural Equation Model using the LISREL program. This study aims to explain the extent to which consumer product involvement, attitudes towards advertising, ad cognition, and perceived value influence consumers’ purchase intentions. This study found that there was a positive relationship between consumer product involvement and attitudes towards ad and ad cognition, and perceived value had an effect on consumer purchase intentions. As a managerial implication, our results can help strategic marketing managers, content creators, and marketers to focus on the identified factors driving advertising effectiveness..